2020
DOI: 10.1519/jsc.0000000000002499
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Heart Rate Variability in Tracking Travel and Training Stress in Youth Female Rowers: A Preliminary Study

Abstract: These insights add value to HRV's use in youth sport and provides coaches with an easy, cost-effective means to monitor the physiological response to training, allowing fine-tuning of training, potentially enhancing performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…The measurement from the first week of training was classified as a baseline recording, taken as described below. During week 6 of the training period, there was a week-long training camp in which training frequency was increased (10 sessions per week compared to 6), and the HRV response to such overload was described previously in a similar population [27]. All HRV measurements were recorded once a week, on the Friday of each training week, and at a consistent time of day (3:00 p.m.) to eliminate any circadian effect on HRV [28,29].…”
Section: Experimental Designmentioning
confidence: 83%
See 2 more Smart Citations
“…The measurement from the first week of training was classified as a baseline recording, taken as described below. During week 6 of the training period, there was a week-long training camp in which training frequency was increased (10 sessions per week compared to 6), and the HRV response to such overload was described previously in a similar population [27]. All HRV measurements were recorded once a week, on the Friday of each training week, and at a consistent time of day (3:00 p.m.) to eliminate any circadian effect on HRV [28,29].…”
Section: Experimental Designmentioning
confidence: 83%
“…Rating of perceived exertion for the week of training was measured before every HR recording using the modified Borg's scale (RPE; 1-10) [33], and was used to calculate training load, as originally described [34]. This method has since been used in similar studies [27], and has been systematically reviewed, supporting its use as a standalone approach [35].…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in training load have been shown to alter the HRV indices [10,[14][15][16][17][18][19][20][21][22]. Pichot et al [10] examined the relationship between HRV and training load in middle-distance runners and indicated that SDNN and RMSSD increased significantly with the decrease in training load during the recovery week.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, along with mean HR, R-R intervals were analyzed for the standard deviation of R-R intervals, SDNN; root mean square of successive differences, RMSSD; and the log transformed RMSSD, LnRMSSD. HRV was measured to assess potential impacts of wrist cooling on recovery as it is an increasingly recognized method to assess or monitor athlete acute and chronic physiological response to training, or recovery and readiness to train [ 22 , 23 , 24 , 25 , 26 ]. After HR and HRV were obtained, to further characterize potential impacts of wrist cooling on recovery, blood pressure (BP) was measured via oscillometric cuff method (Mobilograph, GmbH, Stolberg, Germany) [ 27 , 28 , 29 ], after which thermal sensation/comfort via thermal sensation (TS) scale (0 “unbearably cold” to 8 “unbearably hot”), and fatigue via a visual analog scale (0 “no fatigue” to 10 “severe fatigue”) were recorded.…”
Section: Methodsmentioning
confidence: 99%